CCAFS Business plan 2014 - CGIAR Research Program on Climate Change, Agriculture and Food Security (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2014)
The 2014 business plan of the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) lays out the key activities in 2014, situated within the larger strategic framework of CCAFS.